Association of Fresh Embryo Transfers Compared With Cryopreserved-Thawed Embryo Transfers With Live Birth Rate Among Women Undergoing Assisted Reproduction Using Freshly Retrieved Donor Oocytes - Insogna, Iris G. (JAMA, 2021)
IMPORTANCE: In in vitro fertilization cycles using autologous oocytes, data have demonstrated higher live birth rates following cryopreserved-thawed embryo transfers compared with fresh embryo transfers. It remains unknown if this association exists in cycles using freshly retrieved donor oocytes. OBJECTIVE: To test the hypothesis that in freshly retrieved donor oocyte cycles, a fresh embryo transfer is more likely to result in a live birth compared with a cryopreserved-thawed embryo transfer. DESIGN, SETTING, AND PARTICIPANTS: Retrospective cohort study using national data collected from the Society for Assisted Reproductive Technology for 33 863 recipients undergoing fresh donor oocyte cycles in the US between January 1, 2014 and December 31, 2017. EXPOSURES: Fresh embryo transfer and cryopreserved-thawed embryo transfer. MAIN OUTCOMES AND MEASURES: The primary outcome was live birth rate; secondary outcomes were clinical pregnancy rate and miscarriage rate. Analyses were adjusted for donor age, day of embryo transfer, use of a gestational carrier, and assisted hatching. RESULTS: Recipients of fresh and cryopreserved-thawed embryos had comparable median age (42.0 [interquartile range IQR, 37.0-44.0] years vs 42.0 [IQR, 36.0-45.0] years), gravidity (1 [IQR, 0-2] vs 1 [IQR, 0-3]), parity (0 [IQR, 0-1] vs 1 [IQR, 0-1]), and body mass index (24.5 [IQR, 21.9-28.7] vs 24.4 [IQR, 21.6-28.7]). Of a total of 33 863 recipients who underwent 51 942 fresh donor oocyte cycles, there were 15 308 (29.5%) fresh embryo transfer cycles and 36 634 (70.5%) cryopreserved-thawed embryo transfer cycles. Blastocysts were transferred in 92.4% of fresh embryo transfer cycles and 96.5% of cryopreserved-thawed embryo transfer cycles, with no significant difference in the mean number of embryos transferred. Live birth rate following fresh embryo transfer vs cryopreserved-thawed embryo transfer was 56.6% vs 44.0% (absolute difference, 12.6% [95% CI, 11.7%-13.5%]; adjusted relative risk [aRR], 1.42 [95% CI, 1.39-1.46]). Clinical pregnancy rates were 66.7% vs 54.2%, respectively (absolute difference, 12.5% [95% CI, 11.6%-13.4%]; aRR, 1.34; [95% CI, 1.31-1.37]). Miscarriage rates were 9.3% vs 9.4%, respectively (absolute difference, 0.2% [95% CI, −0.4% to 0.7%]); aRR, 0.98 [95% CI, 0.91-1.07]). CONCLUSIONS AND RELEVANCE: In this retrospective cohort study of women undergoing assisted reproduction using freshly retrieved donor oocytes, the use of fresh embryo transfers compared with cryopreserved-thawed embryo transfers was associated with a higher live birth rate. However, interpretation of the findings is limited by the potential for selection and confounding bias.